The role of ubiquitination and deubiquitination in urological tumours - Gan, Lifeng; Luo, Peiyue; Zou, Junrong; Li, Wei; Chen, Qi; Cheng, Le; Zhang, Fangtao; Zhong, Haidong; Zheng, Liying; Qian, Biao (Frontiers in Pharmacology, 2025)
The ubiquitin (Ub) system has been demonstrated to play a crucial role in various cellular processes, including immune responses, cell development, and programmed cell death. Ubiquitination, a form of post-translational modification, occurs in eukaryotic cells and involves several key components, such as Ub-activating enzymes, Ub-binding enzymes, and Ub-protein ligases. Recently, deubiquitinating enzymes—proteases that reverse the modification of proteins by removing Ub or Ub-like molecules, or by remodeling Ub chains on target proteins—have been identified as significant regulators of ubiquitination-mediated degradation. These enzymes profoundly influence cellular pathways and numerous biological processes, including the DNA damage response and DNA repair mechanisms. Recent studies increasingly demonstrate a relationship between ubiquitination, deubiquitination, and urinary diseases. The roles of these processes in urinary diseases are complex, encompassing various aspects of signaling, protein stability, and cellular metabolism. As research advances, the specific mechanisms by which these processes influence urologic diseases will be further clarified. This review examines recent discoveries in this field, aiming to provide new strategies and targets for the diagnosis and treatment of urologic diseases.